Analysis of the Application of ISAK 35 on Financial Reporting at Jami' Nurul Falah Mosque, Klojen District, Malang City - Catur Pambudi; Dwi Anggarani; Khojanah Hasan (Optima Science, 2024)
This research aims to knowing the suitability of the application of ISAK at the Jami' Nurul Falah Mosque, Klojen District, Malang City, is appropriate in 2021. This arises due to a phenomenon in society, especially non-profit oriented organizations, namely the discrepancy of existing financial statements or those presented by non-profit organizations in contrast to references to ISAK 35 guidelines. The research method carried out is descriptive qualitative, where the data collection used is observation, interviews, and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and conclusion. The setting of the study was carried out at the Jami' Nurul Falah Mosque, Klojen District, Malang City, because the object was considered large enough to implement existing regulations with a large enough turnover of money. The result of this study is that Jami' Nurul Falah Mosque, Klojen District, Malang City has not applied ISAK 35 in the presentation of its financial statements. This happens because there are no experts in preparing financial statements, as well as the absence of socialization to introduce ISAK 35 financial statements to non-profit organizations.